Special Issue - July/August 2023: Emerging Frontiers in Human Experience - Patient Experience Journal (The Beryl Institute, 2022)
Patient Experience Journal (PXJ) is excited to announce the call for submissions for its July/August 2023 special issue focused on exploring the emerging frontiers of human experience in healthcare. As shared in the recent PXJ article, Reexamining "Defining Patient Experience": The human experience in healthcare: "The rapid evolution in the recognition of the humanity in healthcare has required us to view the human healthcare experience not just as a person-centered process or relationship-based encounter. It is an intricate tapestry of human interaction both in the clinical and non-clinical settings across the continuum of care and into the communities served by healthcare organizations around the world. It must take into account the experiences of those who work in healthcare and the experiences communities have with healthcare organizations and systems overall." This perspective pushes us to look beyond the essential questions of what matters to patients, family members or care partners to appreciate how the patient experience is shaped by the needs of the healthcare workforce and the communities they serve around the world. These ideas, reinforced in the recent Declaration for Human Experience (https://transformhx.org/) call on us to think about where the efforts to transform the human experience in healthcare are leading. This special issue is intended to push those boundaries even further.